The Utilization of Artificial Intelligence in Determining the Beginning of Islamic Calendar in Indonesia - Rofiuddin, Ahmad Adib; Ardliansyah, Moelki Fahmi (University of Muhammadiyah Sumatera Utara, 2024)
Recent technological advancement, artificial intelligence (AI), allows for the integration of human intelligence algorithms and application machines. As AI develops, it will be able to assist people in a variety of areas, including business, health, education, and others. The advantages of AI in establishing the start of the Hijri month are one of the benefits that we will discuss in this paper. Muslims, especially Indonesian Muslims, are now highly interested in learning about the Hijri calendar, especially as the months of Ramadan and Shawwal begin. Community organizations have repeatedly criticized the government's determination of the month's beginning in recent years with some argumentation provided. In order to address this issue, we will attempt to apply AI to pinpoint the start of Islamic Calendar especially in these months. This paper shows that in Fiqh and Astronomical Perspectives, Artificial Intelligence cannot be used as the main instrument in determining the beginning of the Islamic Calendar in Indonesia.